2012
DOI: 10.1145/2088883.2088893
|View full text |Cite
|
Sign up to set email alerts
|

Validation of object oriented metrics using open source software system

Abstract: In today's environment the relevance of Free Open Source Software Systems is understood and appreciated both in academia and research. The debate about the pros and cons of the open source vis-à-vis proprietary software has been raging from ages ever since Richard Stallman founded the Free Software Foundation in 1985. With the changing trends in the domain of Object Oriented Systems there is a need to measure the fault predictability of software metrics on open source software systems. In this paper we present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 12 publications
0
23
0
5
Order By: Relevance
“…Interestingly, none of the studies found RFC insignificant but 5 of the studies did not measure RFC. [10], [19], [21], [17], [1], [22], [6], [25], [23], [3], [4], [2], [24], [27], [11], [29], [12], [9], [30], [31], [32], [36], [37] [8] [5], [28], [35], [34], [33] RFC [10], [19], [21], [17], [1], [22], [6], [11], [23], [3], [4], [8], [5], [24], [27], [11], [29], [12], [9], [30], [31], [32], [36], ...…”
Section: Ck and Sloc Metrics Relationship With Fault Pronenessmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, none of the studies found RFC insignificant but 5 of the studies did not measure RFC. [10], [19], [21], [17], [1], [22], [6], [25], [23], [3], [4], [2], [24], [27], [11], [29], [12], [9], [30], [31], [32], [36], [37] [8] [5], [28], [35], [34], [33] RFC [10], [19], [21], [17], [1], [22], [6], [11], [23], [3], [4], [8], [5], [24], [27], [11], [29], [12], [9], [30], [31], [32], [36], ...…”
Section: Ck and Sloc Metrics Relationship With Fault Pronenessmentioning
confidence: 99%
“…With the insignificance results, it show that a class having a higher number of children is not likely to be fault-prone than others with less number of children. The validation for both DIT and NOC are shown in Table 6 [19], [22], [6], [25], [5], [2], [27], [9], [37] [10], [21], [17], [23], [3], [4], [8], [24], [11], [29], [12], [30], [31], [32], [36] [1], [28], [35], [34], [33] NOC [17], [22], [2] [19], [25], [23], [3], [4], [24], [27], [11], [29], [12], [30], [31], [32], [36], [37] [10], [21], [1], [6], [5],…”
Section: Ck and Sloc Metrics Relationship With Fault Pronenessmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 22 studies confirmed WMC significance relationship with the FP of OO classes, one study [2] found considered it to be insignificant while 6 others studies did not consider it their studies.This is captured in Table 3. [10], [40], [17], [1], [22], [6], [25], [23], [3], [4], [8], [2], [24], [27], [11], [29], [12], [31], [32], [35], [36], [37] [2]…”
Section: Ck and Sloc Metrics Relationship With Fault Pronenessmentioning
confidence: 99%
“…In the same vein, 15 studies found it to be insigni¯cant while 5 studies did not measure [11], [28], [4], [5], [29], [30], [34], [7] [ 12], [8], [9], [27], [45] [31], [32], [38], [6], [7], [33], [39], [13], [41], [14], [43], [44], [47], [48] it. With more emphasis, the insigni¯cance of DIT indicates that a class with higher number of inheritance hierarchy is not likely to have faults.…”
Section: Ck + Sloc Metric Relationship With Fpmentioning
confidence: 99%